Rol de la mujer en la pesca ornamental en la cuenca alta media y baja del río Nanay Loreto Perú - Suárez Pizarro, Mercedes Guadalupe (2023)
From October 2022 to February 2023, socio-economic information was obtained from the ornamental fishermen's associations of the Nanay river basin, department of Loreto, Peru. The objective of this study was to know the role of women in the fishing activity in the upper, middle and lower basin of the Nanay River, Department of Loreto, Peru; identifying the state of active participation in their communities; their ages; administrative charges; fishing formalism, and phases of greater participation in the activity of socio-economic development and of high biological and social relevance in the Peruvian Amazon. A participatory methodology was used, through direct interviews and information search in a total of 11 communities in the upper, middle and lower basin of the Nanay River. A total of 218 people dedicated to ornamental fishing were identified, being 63.76% male and 36.24% female; with greater activity on the part of the masculine sex in all the basins analyzed; while in seven communities, women had a greater presence in the activity of ornamental fishing; with ages mainly between 26 and 34 years; administrative positions from members to presidents of the associations and a state of fishing formalization of 26.61%; and having a greater participation within the productive phase in the breeding of ornamental fish (48.54%). In conclusion, the results indicated that the role of the female gender in ornamental fishing in the upper, middle and lower basins of the Nanay River is relevant for socio[1]economic development since it has levels of greater than 30% active participation in fishermen's associations.